The Effect of Quizizz as a Formative Evaluation Tool in History Learning: A Study on Students at MAN 2 Kota Malang - Aji Saputra, Mochammad Ronaldy; Jazuli, Moch (Revorma: Jurnal Pendidikan dan Pemikiran, 2025)
Rapid technological developments and demands for more interesting and interactive learning methods. Quizizz, as one of the popular quiz-based applications, is considered to have the potential to increase student learning motivation and provide teachers with fast feedback. This study aims to measure the effectiveness of using the Quizizz application as a formative evaluation tool for history learning students at MAN 2 Kota Malang. The research method employed is a mixed-methods approach with an explanatory design. Quantitative data were collected through quasi-experiments with a post-test-only control group design. Then, qualitative data were collected by conducting in-depth interviews with students and teachers to understand more deeply the factors that influence the effectiveness of Quizizz. The results of the study indicate that Several questions need to be fixed to match the objectives of measuring HOTS abilities. Quizizz media meets very good quality, namely 100% in the aspects of (1) objectivity, (2) practicality, (3) adaptability, and (4) interest. Quizizz media has been proven effective in increasing student learning motivation, both internally and externally. With an average score of 88 in the experimental group and a significance value of 0.000 in the t-test. Quizizz provides an interesting, interactive, and more motivating evaluation experience than conventional methods, making it an effective alternative for teachers in implementing formative evaluations to increase student learning motivation.